Rider education at Swedish riding schools: Comparing teachers' and pupils' perspectives - Lina Nyberg; Mari Zetterqvist Blokhuis; Andrew McLean; Elke Hartmann (PLoS ONE, 2026)
Previous research has highlighted a gap between scientific evidence and its application in equestrian practice, leading to concerns about horse welfare and human safety. Riding schools present an important platform for promoting science-based practices, as they bring together riders of all ages and levels and serve as sites for equestrian education and for shaping attitudes toward horse welfare. Yet, the teaching in riding schools is often rooted in traditional practices. Therefore, mapping current educational methods and exploring how teaching and learning are perceived by both riding school teachers and pupils are key to supporting schools in bridging the gap between tradition and evidence-based practices. This study aimed to map how equestrian knowledge, with a specific focus on horse behaviour and welfare (BW), and horse learning and human-horse communication (LC), is taught and perceived to be learned, drawing on the perspectives of both teachers and pupils. Data collection was based on two online surveys, distributed to approximately 450 Swedish riding schools (RS) under the Swedish Equestrian Federation. The survey links were shared via the Federation’s newsletter, as well as through social media, horse magazines, and relevant equestrian websites. The surveys collected responses from 199 teachers and 368 pupils. The results showed that most teachers (83%) integrated BW and LC into regular riding lessons and 59% provided such education outside riding lessons. Yet, only 21% of the teachers believed that pupils learn enough when BW and LC are taught in connection with other teaching occasions. While 71% of pupils expressed interest in dedicated BW and LC lessons, only 24% of teachers thought pupils were interested in attending. The main barrier to offering separate lessons, according to teachers, was perceived lack of interest (50%), whereas 30% of pupils cited the unavailability of such lessons. These differing perceptions highlight the need for improved communication and greater alignment between teaching practices and what learners find engaging. The findings from this study offer a foundation for developing strategies to better support evidence-based equestrian education at riding schools.